A Plastic Surgeon's Guide to the Temporomandibular Joint: Part I, Anatomy. Issue 2 (June 2023) - Buller, Mitchell; Ibelli, Taylor J.; Mantilla-Rivas, Esperanza; Platt, Samantha; Doo, Florence; Crowder, Hannah R.; Nasser, Jacob S.; Rogers, Gary F.; Taub, Peter J.; Alex Rottgers, S.
The temporomandibular joint (TMJ) is a critical articulation between the mandible and cranium. The unique anatomy allows for a multifaceted motion unlike any other joint in the human body. The bi-convex curvature of the bony prominences facilitates a compound hinging and sliding movement, which are driven by the muscles of mastication and constrained by various ligamentous connections surrounding the joint. Proper alignment and function of these structures are essential to ensure a relationship between the mandibular and maxillary dental arches and fluid motion of the mandible during mastication. While the versatile form and function of the TMJ allow for coordinated jaw movements, pathologic conditions can lead to dysfunction and pain. Therefore, understanding the anatomy and associated pathophysiology of the TMJ is critical for a plastic surgeon who manages craniomaxillofacial trauma and disorders. The present manuscript is the first of a 3-part series with an overview of the TMJ anatomy. Subsequent sections will address the pathology and the treatment of various TMJ disorders.